Effect of Flood Water Diffuser on Flow Pattern of Water during Road Crossing - Abdul Ghani, A.N.; Kasnon, N. (EDP Sciences, 2014)
One of the methods to reduce the velocity of flood water flow across roads is to design obstacle objects as diffusers and place them alongside the road shoulder. The velocity reduction of water flow depends on the diffusion pattern of water. The pattern of diffused water depends on the design of the obstacle objects. The main purpose of this study is to investigate the design of obstacle objects and their water diffusing patterns and their capability to reduce the velocity of the flood water flow during road crossing. Variety of designs and orientation of the obstacle objects were tested in the environmental laboratory on a scale of 1:20. The results are classified into three distinguishable patterns of diffusion. Finally, two diffuser shapes and arrangements are recommended for further investigations in full scale or CFD model.